Design optimization of CdTe/Si tandem solar cell using different transparent conducting oxides as interconnecting layers - Isah M.; Rahman K.S.; Doroody C.; Harif M.N.; Rosly H.N.; Sopian K.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Cadmium telluride; Computer software; Cost effectiveness; Design; Efficiency; II-VI semiconductors; Numerical models; Silicon solar cells; Transparent conducting oxides; CdTe layers; CdTe/Si; Cost effective; Design optimization; Efficiency limits; Inter-connecting layers; Multi-junctions; Single junction solar cells; Tandem solar cells; Transparent conducting oxide; Silicon